2020
DOI: 10.1037/amp0000600
|View full text |Cite
|
Sign up to set email alerts
|

Established adulthood: A new conception of ages 30 to 45.

Abstract: In developed countries, the years from Age 30 to 45 are, for many, the most intense, demanding, and rewarding years of adult life. During this period of the life span most adults must negotiate the intersecting demands of progressing in a chosen career, maintaining an intimate partnership, and caring for children. Successes or difficulties in meeting these simultaneous demands have the potential to profoundly influence the direction of a person's adult life. As such, we believe that it is of critical importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 64 publications
4
150
0
3
Order By: Relevance
“…Adults were stratified into the following age groups: young adulthood (Group 1: ages 18-39; M age = 30.72, SD = 6.05, N = 854, middle adulthood (Group 2: ages 40-64; M age = 50.6, SD = 6.5, N = 1,848) and older adulthood (Group 3: ages 65-75; M age = 70.6, SD = 5.05, N = 250). We selected these age groupings based on a priori, developmental life stage considerations that have been underscored as important in recent research (Mehta et al, 2020); although there is no 'validated' age cutoff, the age groupings chosen in our study are generally accepted within the developmental literature as they coincide with social and psychological resource changes as well as biological changes in adult development (Robert & Feldman, 2019). Specifically, young adulthood (ages 18-39) is generally characterized by transitioning to a committed romantic partnership (and typically marriage), new parenthood, building a career while balancing multiple professional and family roles, and overall good physical health (Mehta et al, 2020;Robert & Feldman, 2019).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults were stratified into the following age groups: young adulthood (Group 1: ages 18-39; M age = 30.72, SD = 6.05, N = 854, middle adulthood (Group 2: ages 40-64; M age = 50.6, SD = 6.5, N = 1,848) and older adulthood (Group 3: ages 65-75; M age = 70.6, SD = 5.05, N = 250). We selected these age groupings based on a priori, developmental life stage considerations that have been underscored as important in recent research (Mehta et al, 2020); although there is no 'validated' age cutoff, the age groupings chosen in our study are generally accepted within the developmental literature as they coincide with social and psychological resource changes as well as biological changes in adult development (Robert & Feldman, 2019). Specifically, young adulthood (ages 18-39) is generally characterized by transitioning to a committed romantic partnership (and typically marriage), new parenthood, building a career while balancing multiple professional and family roles, and overall good physical health (Mehta et al, 2020;Robert & Feldman, 2019).…”
Section: Participantsmentioning
confidence: 99%
“…We selected these age groupings based on a priori, developmental life stage considerations that have been underscored as important in recent research (Mehta et al, 2020); although there is no 'validated' age cutoff, the age groupings chosen in our study are generally accepted within the developmental literature as they coincide with social and psychological resource changes as well as biological changes in adult development (Robert & Feldman, 2019). Specifically, young adulthood (ages 18-39) is generally characterized by transitioning to a committed romantic partnership (and typically marriage), new parenthood, building a career while balancing multiple professional and family roles, and overall good physical health (Mehta et al, 2020;Robert & Feldman, 2019). By middle adulthood (ages 40-64), individuals often acquire career expertise and reach occupational and economic stability, launch their adult children into independence, care for their aging parents and experience gradual decrements in physical health (e.g.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study also found that change across the two-year period was significantly heritable (15% on average), suggesting that genetic influences change even during this two-year period in the early years of emerging adulthood. It remains to be seen whether the heritability of EA traits increases as the sample fully emerges into what has been called established adulthood (Mehta, Arnett, Palmer, & Nelson, 2020). The importance of non-shared environment in emerging adulthood is clear: it accounted for 82% of the variance on average for change across the two-year period.…”
Section: Discussionmentioning
confidence: 99%
“…There are also more recent arguments to consider the period between the ages of 30 and 45 as established adulthood (Mehta et al, 2020): a stage of special importance not only for the three vital developmental challenges of adulthood: work, relationships, and parenthood, but also for creativity (see Mehta et al, 2020).…”
mentioning
confidence: 99%